Virtual Screening For Identifying A Putative Inhibitor Of Rmlc, A Major Target Protein In Tuberculosis Disease - SHEFIN B; BINDU A. SUNILKUMAR (International Journal of Pharma and Bio Sciences, 2015)
Tuberculosis, is caused by various strains of Mycobacteria, and specifically the one by Mycobacterium tuberculosis needs effective treatment. Administration of antibiotics fails owing to multi-drug resistant capability of Mycobacterium. Traditional methods for the identification of a potential drug take time and require huge investment The present study was focused on virtual screening to identify an effective drug candidate against tuberculosis. RmlC protein, an important enzyme of the rhamnose pathway for bacterial pathogenicity is selected, as the target molecule. Inhibition of the RmlC protein function was achieved by docking with 1200 ligand molecules using GOLD software. Finally, five leads were identified with a GOLD score above 90. Hydrogen bonding pattern, Lipinski’s rule, and Drug likeliness test of the potential leads were determined. On the basis of screening it can be summarized that the identified compounds can be further studied for their potentiality as suitable drug candidates.